The Epidemiology of Vertigo, Dizziness, and Unsteadiness and Its Links to Co-Morbidities - Bisdorff, Alexandre; Bosser, Gilles; Gueguen, René; Perrin, Philippe (Frontiers in Neurology, 2013)
Vertigo, dizziness and unsteadiness (VDU) are common symptoms traditionally considered to result from different kinds of vestibular and non-vestibular dysfunctions. The epidemiology of each symptom and how they relate to each other and to migraine, agoraphobia, motion sickness susceptibility (MSS), vaso-vagal episodes (VVE) and anxiety-depression (AD) was the object of this population-based study in north-eastern France. A self-administered questionnaire was returned by 2987 adults (age span 18-86 years, 1471 women). The 1-year prevalence for vertigo was 48.3%, for unsteadiness 39.1% and for dizziness 35.6%. The three symptoms were correlated with each other, occurred mostly (69.4%) in various combinations rather than in isolation, less than once per month, and 90% of episodes lasted ≤ 2 minutes. The three symptoms were similar in terms of female predominance, temporary profile of the episodes and their link to falls and nausea. Symptom episodes of >1 hour increase the risk of falls. VDU are much more common than the known prevalence of vestibular disorders. The number of drugs taken increase VDU even when controlling for age. Each VDU symptom was correlated with each co-morbidity in Chi2 tests. The data suggest that the three symptoms are more likely to represent a spectrum resulting from a range of similar — rather than from different, unrelated — mechanisms or disorders. Logistic regressions controlling for each vestibular symptom showed that vertigo correlated with each co-morbidity but dizziness and unsteadiness did not, suggesting that vertigo is certainly not a more specific symptom than the other two. A logistic regression using a composite score of VDU, controlling for each co-morbidity showed a correlation of VDU to migraine and VVE but not to MSS and not to agoraphobia in men, only in women.